2020
DOI: 10.1519/jsc.0000000000003616
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Knee Muscle Capacity Is Correlated With Impaired Sagittal Kinematics During Jump Landing in Women With Patellofemoral Pain

Abstract: Nunes, GS, Barton, CJ, and Serra ˜o, FV. Impaired knee muscle capacity is correlated with impaired sagittal kinematics during jump landing in women with patellofemoral pain. J Strength Cond Res 36(5): 1264-1270, 2022-Knee and hip muscle capacity is impaired in women with patellofemoral pain (PFP), but little is known about the rate of force development (RFD) at the knee. Impaired muscle capacity may contribute to reduced sagittal plane movement at the knee and hip during jump landing in women with PFP. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Moreover, people with PFP present other proximal and knee muscle capacity de cits, such as rate of force development (RFD) and power [12][13][14][15]. Nunes et al [12,13] reported lower hip abductor and extensor, and knee extensor rate of force development (RFD) during maximal isometric contraction in women with PFP compared to women without PFP. Similarly, according to the study by Ferreira et al [15], women with PFP have lower hip abductor and knee extensor RFD during isometric, concentric and eccentric contractions compared to women without PFP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, people with PFP present other proximal and knee muscle capacity de cits, such as rate of force development (RFD) and power [12][13][14][15]. Nunes et al [12,13] reported lower hip abductor and extensor, and knee extensor rate of force development (RFD) during maximal isometric contraction in women with PFP compared to women without PFP. Similarly, according to the study by Ferreira et al [15], women with PFP have lower hip abductor and knee extensor RFD during isometric, concentric and eccentric contractions compared to women without PFP.…”
Section: Discussionmentioning
confidence: 99%
“…Although these recent studies have shown that patients with PFP have hip and knee muscle power de cits [12][13][14][15], little is known in relation to power training effects in these people. Until the moment, only two studies included power exercises for the treatment of these patients [30,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There will be a 4 min rest period between each test at two different speeds 51. Participants will be urged to exert themselves to the fullest during the test,52 and the results, recorded in Newton-metres, Newton-metres/kg and watts, will be calculated as the peak torque, peak torque per kilogram of body weight and power. Research has shown that the reliability of knee muscle strength assessment using the isokinetic method is 0.94 in test–retest scenarios 53.…”
Section: Methods and Analysismentioning
confidence: 99%